Faktor-Faktor yang Berhubungan Dengan Kepatuhan Minum Obat Pada Pasien Skizofrenia Di Poliklinik Jiwa Rumah Sakit Budi Kemuliaan Kota Batam - Nopri Esmiralda; Sukma Sahreni; Bella Aprillia (Universitas Batam, 2022)
Background :Schizophrenia is one of the most serious and disturbing mental disorders. Mental disorders are a very serious problem in the world. Management of schizophrenia requires long-term medication to keep symptoms under control and to prevent relapse. Methods : This research is an observational analytic study with a cross sectional research design. This research was conducted at the Mental Polyclinic of Budi Kemuliaan Hospital Batam in Juni 2021. The population of this study were families and patients with paranoid type of schizophrenia with a total sample of 60 people. The sampling method is Accidental Sampling. The instrument used is a questionnaire. Data analysis using Fisher's exact test. Result : The results of this study found that age, gender, education, occupation, length of treatment and family support had a relationship with medication adherence in schizophrenic patients, while marital status had no relationship with medication adherence in schizophrenic patients. Fisher's statistical test results obtained age with p value 0.000, gender p value 0.006, marital status p value 0.844, education p value 0.020, occupation p value 0.004, duration of treatment p value 0.018 and family support p value 0.000. Conclusion : Based on the results of data processing, it can be concluded that there is a significant relationship between age, gender, education, occupation, duration of treatment and family support with medication adherence in schizophrenic patients and there is no significant relationship between marital status and medication adherence in schizophreni.